Can Domino Card Be Effective in Elementary School Instruction? - Nanda Azahra; Sri Enggar Kencana Dewi (Elementary Education Journal, 2022)
Background:The problem in this study is whether there is an effect of using domino card media on student learning outcomes. The purpose of this study was to obtain information about student learning outcomes by using domino cards as media. Method:The research method used in this study was a quasi-experimental design with a nonequivalent control group research design. This study used two classes, namely VA and VB classes. From the research results, it was found that in the experimental class the average value was 84.77 while in the control class the average value was 72.15. The results of the independent sample t-test obtained a sig. 2 tailed is 0.000 <0.05, it is known that there is a significant difference between the average learning outcomes in groups A and B. Results: Based on the results of the analysis of the data obtained, it was concluded that learning by using domino card learning media can have an influence on student learning outcomes in Theme 6 Sub-theme 2 Learning 1 and 2 which can be seen from the difference in average learning outcomes in the experimental class and the control class.